On the Volatility of S&P CNX NIFTY - Sen, Som Sankar (Indian Journal of Finance, 2010)
The financial system of a country is expected to work in a way that facilitates the channelisation of resources from the surplus sectors to the deficit sectors which have a pressing need for them. This is needed with a view to ensure growth in the economy. In order to do this an economy needs a vibrant stock market which would ensure safety, integrity and liquidity to the investing community which makes investments in wide range of financial instruments. Studies conducted by Singh (1997), Levine and Zervos (1998) reveal that being a part of the financial system, stock markets play a crucial role to the economic growth of a country.